Differential Effects of the Auditory Intellectually Repetition (AIR) Model on Students’ Critical Thinking Skills: A Gender-Based Analysis in Environmental Change Learning - Barata, Muhammad Farhan; Aisyah, Suci Nur; Epandi, Dafa (ISEJ : Indonesian Science Education Journal, 2025)
The development of critical thinking skills is a key objective in 21st-century science education, particularly in learning contexts involving complex environmental issues. However, students’ critical thinking abilities remain relatively low due to the dominance of teacher-centered instructional practices. This study aims to examine the effectiveness of the Auditory, Intellectually, and Repetition (AIR) learning model in enhancing students’ critical thinking skills in environmental change and conservation learning, as well as to analyze differences based on gender. A quasi-experimental method with a non-equivalent control group pretest–posttest design was employed, involving 73 tenth-grade students divided into experimental and control classes. Data were collected using an essay-based critical thinking test developed based on Ennis’ indicators, including interpretation, analysis, evaluation, inference, and explanation. The results indicate that students in the experimental group achieved significantly higher posttest scores (M = 88.19) and N-Gain (g = 0.72, high category) compared to the control group (M = 60.88; g = 0.21, low category). Improvement was observed across all critical thinking indicators, with the highest gains in advanced clarification and basic skill development. Two-way ANOVA results reveal that the instructional model has a significant effect on students’ critical thinking skills (p < 0.05), while gender and the interaction between model and gender are not statistically significant. These findings demonstrate that the AIR model is effective and inclusive for both male and female students. The study implies that integrating active, discussion-based, and reinforcement-oriented learning models with environmental contexts can enhance students’ higher-order thinking and support meaningful engagement with sustainability issues.